2002
DOI: 10.1002/jrs.924
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra and surface‐enhanced resonance Raman scattering of palladium phthalocyanine evaporated films

Abstract: The vibrational spectra of palladium phthalocyanine (PdPc) evaporated thin solid films are reported, including the resonance Raman scattering, surface-enhanced resonance Raman scattering (SERRS) and SERRS mapping of the film surface using micro-Raman spectroscopy with 633 nm laser radiation. SERRS of PdPc was obtained by evaporating an overlayer of Ag nanoparticles on to the PdPc film on glass. The SERRS enhancement factor is estimated as ∼10 4 with reference to PdPc evaporated films on glass. The molecular or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
2
23
1
4
Order By: Relevance
“…The bands at 729 cm -1 are attributed to C-H wagging (FePc macrocycle out-of-plane), while the bands at 1117 and 1331 cm -1 are assigned, respectively, to C-H in-plane deformation and CdC or CdN stretching (pyrrol), also in the plane of the FePc macrocycle. 25,26,31,32 The C-H wagging is relatively intense in all the spectra (KBr pellet and PVD films), and dominates the FTIR-reflection spectrum. This difference in the relative intensity for the transmission and reflection modes reveals anisotropy in the molecular organization of FePc in the PVD films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands at 729 cm -1 are attributed to C-H wagging (FePc macrocycle out-of-plane), while the bands at 1117 and 1331 cm -1 are assigned, respectively, to C-H in-plane deformation and CdC or CdN stretching (pyrrol), also in the plane of the FePc macrocycle. 25,26,31,32 The C-H wagging is relatively intense in all the spectra (KBr pellet and PVD films), and dominates the FTIR-reflection spectrum. This difference in the relative intensity for the transmission and reflection modes reveals anisotropy in the molecular organization of FePc in the PVD films.…”
Section: Resultsmentioning
confidence: 99%
“…There is now a surge on their use for devices, for example, in photocopiers, solar cells, electrochromic displays, fuel cells, light-emitting diodes, transistors, optical limiters, in photodynamic therapy, [6][7][8][9][10][11][12][13][14][15][16][17][18] and sensors. 15,[19][20][21] In several of the possible applications, one important requirement is to produce materials in the form of thin films, which has been carried out for phthalocyanines with various methods, including Langmuir-Blodgett (LB), [22][23][24][25][26] electrostatic layer-bylayer (LbL), [27][28][29][30] physical vapor deposition (PVD), 31,32 and casting. 33 For sensing, in particular, it has been shown that film morphology and surface properties are relevant for the sensor performance.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest peak oabtained at 1108 cm À1 is attributed to C-H bond in plane bending and Ca-Cb bond stretching in FePc. In addition, the strong peak observed at 1330 cm À1 corresponds to C¼C or C¼N stretching vibrations in the pyrrole ring in the plane of the FePC macrocycle [31][32][33]. Another strong peak observed at 1517 cm À1 is attributed to the expansion of pyrrole rings as well as Ca-N c -Ca and C-N m stretching [30].…”
Section: Resultsmentioning
confidence: 82%
“…4,177 No nosso caso, a presença de um terceiro máximo e a diferença de energia entre esses máximos de absorção (dentro décimos de eV) sugerem transições a partir do nível fundamental para diferentes níveis vibracionais do primeiro estado eletrônico excitado. Além disso, o deslocamento para o azul dos máximos de absorção do filme PVD em relação aos máximos de absorção para a solução sugere uma existe organização molecular nos filmes e ainda formação de agregados moleculares tipo agregados H. 16,19,168 Espalhamento Raman e espalhamento Raman amplificado em superfície no pó e nos filmes. 178 Por exemplo, em vários trabalhos na literatura são reportados os efeitos da fabricação de filmes pela técnica PVD na estruturação molecular da ftalocianina.…”
Section: Caracterização Dos Filmesunclassified
“…As técnicas que podem ser citadas são: LbL, 13,14 deposição física de vapor (PVD), quer por evaporação térmica, 15,16 ou sputtering, 17 e ainda LB, 18,19 eletrodeposição, 20 spin-coating 21 e casting. 22 Promissoras aplicações tecnológicas têm sido sugeridas para ftalocianinas na forma de filmes finos em diodos emissores de luz, 23 transistores, 24 células solares, 13 cristais líquidos, 25 células combustível 26 e sensores.…”
Section: Introductionunclassified